Combined Venlafaxine and Olanzapine Prescription in Women with Psychotic Major Depression: A Case Series. (3rd March 2011) - Ghio, Lucio; Natta, Werner; Rossi, Paola; Peruzzo, Laura; Zanelli, Elisa; Gotelli, Simona; Gabrielli, Filippo
Abstract : Patients with psychotic major depression suffer prolonged duration and greater severity of illness, including an increased likelihood of recurrent episodes and resistance to conventional pharmacotherapies. They do not respond to placebo and respond poorly to antidepressant or antipsychotic monotherapy. On the other hand, as has been demonstrated, they do respond well to antidepressant and antipsychotic combination therapies. Different combinations of drugs were studied, but little is known up to now with regard to the combination of venlafaxine and olanzapine. The following paper presents three separate case studies of female patients suffering from psychotic unipolar major depression, all of whom were admitted to a psychiatric ward and successfully treated with a combination of venlafaxine and olanzapine.